ASSESSMENT OF NORMAL SPLEEN SIZE - MOHAMMAD ASLAM SIDDIQUI; ALI HASSAN A. ALI (International Journal of Pharma and Bio Sciences, 2015)
Determination of abnormal changes in size of organs during diseases entails knowing the normal range of their dimensions in healthy individuals. This review discusses the use of different methods over time to assess normal splenic volume in different populations of different parts of the world. It also oversees the normal size of spleen proposed by various researchers. This consideration has become more relevant in recent years, as doctors are keen to know the level of the involvement and or secondary effects of a disease process on spleen. Besides they want to know the progress of a disease process and/ or effect of a treatment plan by evaluating the splenic volume. A structured literature search was conducted on PubMed (Medline), Google Scholar, Embase and other databases till December, 2014to look for studies reporting normal spleen size using various techniques. There is a large range of normal splenic dimensions among individuals. Among the different techniques employed for assessment of normal or otherwise spleen size, ultrasonographic measurements have been considered to be the most feasible and accurate. Ultrasonography can be a useful technique as it is noninvasive and does not involve any risk of radiation. Ultrasound, therefore, has become the most common practice to differentiate pathologically enlarged or reduced spleen in patients.